What is the purpose of “multipurpose forces”? The case of the Colombian armed forces in the “post-agreement” - Saint-Pierre, Héctor Luis; Ferreyra, Matías Daniel (Revista Brasileira de Estudos de Defesa, 2020)
In this article, we analyze possible models of military modernization to Colombia from the “post-agreement” stage initiated with the guerrilla group FARC, considering implications on management and perception in the domestic, regional, and global order. We contemplate the “Multimission Force” model and the “Specialized Force” model, to conclude the latter as the best fit for Colombia and that could be mirrored to all of Latin America.